Management of acute coronary syndrome in older adults (data from russian federal acute coronary syndrome registry) - E V Ocshepkova; O V Sagaydak; I E Chazova (Терапевтический архив, 2018)
The frequency of cardiovascular diseases is increasing progressively with age, and the global aging of the population poses the problem of treatment of patients of older age groups in a row with other relevant medical and socio-economic problems. Aim. In the present study was to investigate the quality of medical care for patients with acute coronary syndrome (ACS) old age and compliance of the treatment current guidelines. The data is exported from the system of the Federal register OKS. Materials and methods. Analyzed medical history 33 893 patients with ACS entered in the system registry of ACS for the period from 01.01.2016 to 31.12.2016. a comparison was made of the quality of care in patients with ACS elderly (75 years and older, n=8773) and in younger patients. Results. The results of the study showed that in patients of senile age, when compared with younger patients, comorbid conditions are significantly more often observed, as well as a significantly higher risk of hospital and 6-month death, calculated on the GRACE scale. Conclusion. Patients of senile age with ACS are almost twice less likely to undergo percutaneous coronary interventions than younger ones, which worsens the prognosis in these patients and increases mortality.